2002
DOI: 10.1590/s0103-84782002000200018
|View full text |Cite
|
Sign up to set email alerts
|

Meningoencefalite Necrosante Em Bovinos Causada Por Herpesvírus Bovino No Estado De Mato Grosso, Brasil

Abstract: Achados epidemiológicos, clínicos, patológicos e microbiológicos de 13 casos de meningoencefalite necrosante pelo Herpesvírus Bovino (BHV), afetando 12 rebanhos bovinos ocorridos no período de março de 1999 a agosto de 2000 em 11 municípios do Estado de Mato Grosso são descritos. Onze surtos ocorreram em sistemas de criação extensiva, afetando com maior freqüência animais da raça nelore, e idade média de 24 meses com uma variação de dois a 72 meses. Os principais sinais clínicos descritos foram as alterações n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
19
3
84

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(112 citation statements)
references
References 10 publications
6
19
3
84
Order By: Relevance
“…Similar to our study, in which 6 out of 7 positive areas with intranuclear inclusion bodies also demonstrated malacia, the presence of intranuclear inclusion bodies has been associated with accentuated inflammation (Colodel et al 2002, Elias et al 2004) and areas with malacia (Elias et al 2004). …”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Asupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to our study, in which 6 out of 7 positive areas with intranuclear inclusion bodies also demonstrated malacia, the presence of intranuclear inclusion bodies has been associated with accentuated inflammation (Colodel et al 2002, Elias et al 2004) and areas with malacia (Elias et al 2004). …”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Asupporting
confidence: 90%
“…Mild or moderate nonsuppurative meningitis has been described in cases of BHV-5 infection in cattle (Lunardi et al 2009), restricted to the anterior and posterior cerebral cortex (Perez et al 2002). However, in previous cases of BHV-5 infection this lesion was not reported (Cascio et al 1999, Colodel et al 2002. Cases of BHV-5 infection with polymorphonuclear infiltration in the brain have been reported (Elias et al 2004, Rissi et al 2006, but this pathological finding was not observed in the present study.…”
Section: Fig2 Adjusted Geometric Means* Of Lesions Distributed By Acontrasting
confidence: 68%
“…In this outbreak, the variation in the duration of the BoHV-5 nervous disease ranged from 18 hours to 21 days. These results were slightly higher than those related in other studies, which have ranged from 1 to 15 days (Salvador et al, 1998;Colodel et al, 2002;Elias et al, 2004;Riet-Correa et al, 2006;Rissi et al, 2006). Additionally, the association of each of the different BoHV-5 nervous forms of disease with a specific age was not verified in this outbreak (Table 1).…”
Section: Resultscontrasting
confidence: 75%
“…While BoHV-1 is the etiological agent of infectious bovine rhinotracheitis (IBR), and rarely causes neurological signs, BoHV-5 has been classically considered the causal agent of meningoencephalitis in young cattle of specific geographical areas, mainly Brazil, Argentina, the U.S. and Australia (Johnston et al, 1962;Carrillo et al, 1983;D'Offay et al, 1993;Salvador et al, 1998;Colodel et al, 2002). In Brazil, the occurrence of the disease has been reported in several geographic regions, with cases and/or outbreaks reported in the northern (RietCorrea et al, 2006), central western (Salvador et al, 1998;Colodel et al, 2002), southeastern (Salvador et al, 1998;Gomes et al, 2002), and southern regions (Claus et al, 2007;Rissi et al, 2008). The neurological signs observed in BoHV-5 infections are often multifocal deficits and comprise mainly cerebral and brainstem dysfunctions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation